MHealth: providing a mindfulness app for women with chronic pelvic pain in gynaecology outpatient clinics: qualitative data analysis of user experience and lessons learnt. Issue 3 (12th March 2020) - Ball, Elizabeth; Newton, Sian; Rohricht, Frank; Steed, Liz; Birch, Judy; Dodds, Julie; Cantalapiedra Calvete, Clara; Taylor, Stephanie; Rivas, Carol
Abstract : Objectives: To determine whether a pre-existing smartphone app to teach mindfulness meditation is acceptable to women with chronic pelvic pain (CPP) and can be integrated into clinical practice within the National Health Service (NHS) CPP pathways, and to inform the design of a potential randomised clinical trial. Design: A prestudy patient and public involvement (PPI) group to collect feedback on the acceptability of the existing app and study design was followed by a three-arm randomised feasibility trial. In addition, we undertook interviews and focus groups with patients and staff to explore app usability and acceptability. We also obtained participant comments on the research process, such as acceptability of the study questionnaires. Setting: Two gynaecology clinics within Barts Health NHS, London, UK. Participants: Patients with CPP lasting ≥6 months with access to smartphone or personal computer and understanding of basic English. Intervention: The intervention was mindfulness meditation content plus additional pain module delivered by a smartphone app. Active controls received muscle relaxation content from the same app. Passive (waiting list) controls received usual care. Main outcome measures: Themes on user feedback, app usability and integration, and reasons for using/not using the app. Results: The use of the app was low in both active groups. Patients in the prestudy PPI group, all volunteers, were enthusiastic about the app (convenience, content, portability, flexibility, ease of use). Women contributing to the interview or focus group data (n=14), from a 'real world' clinic (some not regular app users), were less positive, citing as barriers lack of opportunities/motivation to use the app and lack of familiarity and capabilities with technology. Staff (n=7) were concerned about the potential need for extra support for them and for the patients, and considered the app needed organisational backing and peer acceptance. Conclusion: The opinions of prestudy PPI volunteers meeting in their private time may not represent those of patients recruited at a routine clinic appointment. It may be more successful to codesign/codevelop an app with typical users than to adapt existing apps for use in real-world clinical populations. Trial registration number: ISRCTN10925965 .